Seasonal Variation of Heavy Metal Distribution of Water and Sediments in Krishnagiri Dam, Krishnagiri District, Tamil Nadu, India - Prabhahar, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Dams near urban centers are under increasing developmental pressure for residential, industrial and commercial facilities, increasing population and economic growth create high demand for real estate in sub-urban localities is suitable becomes exhausted, pressure intensifies to develop lakes for residential housing, manufacturing plants, business office complexes and similar uses. In the present study, hydro biological characteristic features of the Krishnagiri reservoir Dam, the dates for the present study were collected from 3 sampling stations for the period of 6 months in both premonsoon and monsoon seasons. Totally 5 metals were estimated (Cu, Zn, Cd, Pb, Fe). Among which Fe showed high values followed by Cu, Cd and Zn. The sample analysis was done by microwave assisted digestion and Atomic Absorption Spectrophotometer (AAS).